Facilitating L2 writers’ metacognitive strategy use in argumentative writing using a process-genre approach - Huang, Yu; Zhang, Lawrence Jun (Frontiers in Psychology, 2022)
This paper reports on an empirical study that examined changes in L2 writers' perceived use of metacognitive strategies after receiving a process-genre writing instruction. Following a mixed-methods approach, this study was conducted in two intact College English classes at a university in China. Participants were 72 first-year undergraduates, with an experimental group (n=40) taught by the process-genre writing approach and a comparison group (n=32) receiving conventional writing instruction. A Likert-scale questionnaire was used to examine students' changes in their conceptualised metacognitive strategies. Think-aloud protocols were conducted to gain an in-depth understanding of students' application of metacognitive strategies and genre knowledge in performing writing tasks. Findings revealed that the process-genre instruction had a significantly positive impact on the "considering the audience" factor, and students' conception of the audience was clearer and more diversified. An in-depth analysis of the think-aloud protocols showed that the participants incorporated the acquired metacognitive strategies and genre knowledge in completing writing tasks, with more pre-task planning time focused on both global and local aspects. Students’ metacognitive monitoring also shifted from surface-level lexical and grammar regulation to discourse-level text control.